Chromosomal imbalances in carcinoma showing thymus-like elements (CASTLE) - Veits, Lothar; Mechtersheimer, Gunhild; Steger, Christina; Freitag, Jens; Mikuz, Gregor; Schmid, Kurt W.; Hofmann, Walter; Schirmacher, Peter; Hartmann, Arndt; Rieker, Ralf Joachim (Virchows Archiv, 2011)
Carcinoma showing thymus-like elements (CASTLE) is a rare neoplasm of the thyroid gland resembling lymphoepithelioma-like and squamous cell carcinoma of the thymus and is thought to arise from ectopic thymic tissue within the thyroid gland or rudimentary branchial pouches along the thymic line. Using comparative genomic hybridization (CGH), chromosomal imbalances have been detected in several types of thymomas and thymic carcinomas. To evaluate whether there are hints of an underlying sequence in the pathogenesis of CASTLE analogue to those found in thymomas and thymic carcinomas, we evaluated four of these rare neoplasms for chromosomal imbalances using CGH. The most frequent gains were seen on chromosomal arm 1q (3/4), and losses were most frequently detected on 6p (4/4), 6q (3/4) and 16q (3/4). These CGH data show that CASTLE is characterized by chromosomal imbalances similar to those found in thymomas and thymic carcinomas and indicate a similar sequence in tumour development.